Studi Deskriptif Linimasa Prestasi Atlet Bolavoli Universitas Negeri Malang - Ghafar Assidiqqi, Muhammad; Rahayuni, Kurniati; Widiawati, Prisca; Roesdiyanto, Roesdiyanto (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
This research aims to describe the career path of achievement of volleyball student-athletes from the State University of Malang based on the chronological timeline of achievements in the volleyball championship. This research uses visual research methods (VRM), where data is processed into visual form, namely a timeline graph of achievements. The participants are men's and women's volleyball athletes from the State University of Malang class of 2018-2020 from various faculties with active student status. The achievement data were collected using a questionnaire and given to athletes digitally through Google Forms, then their answers were visualized in timeline graphs. The timeline graphs show the record of athlete achievements chronologically from high school (or equivalent) to college. The graphs were produced and then analyzed using qualitative content analysis. The results showed three patterns in the timeline of athlete achievements: 1) progressive/increase pattern, 2) descending patterns, and 3) stagnation patterns. Implications of this study are: 1) beneficial to understand what factors affect changes in athlete achievements, 2) as reminders for athletes to keep tracking their achievements and develop strategies to improve them; 3) as input for coaches to develop future training programs to improve student-athlete achievement.